"Love Is a Choice": Couple Responses to Continuing Pregnancy With a Lethal Fetal Diagnosis. (January 2018) - Côté-Arsenault, Denise; Denney-Koelsch, Erin
While it is known that couples experience pregnancy differently from one another, the circumstance of continuing pregnancy after learning of a lethal fetal diagnosis has received little attention. This longitudinal, naturalistic study of 16 mothers and 14 spouses/partners aimed to describe pregnant couples' responses and relationships in continued pregnancy with lethal fetal diagnosis and to examine similarities and differences within those couple responses. Individual and joint interviews with parents were conducted across pregnancy, birth, and death of the baby. Within and across couple analysis was performed. Three categories emerged (Pregnant vs. Not Pregnant; Individual Responses to Adversity; Strength of the Couple Relationship) with 12 themes. Findings indicate that individual responses to these stressful pregnancies were inherent in who was physically pregnant, choosing whether to love and embrace the unborn baby, personal characteristics, and the strength of the couple relationship. Care providers should assess couple dynamics. Couples with committed relationships, shared decision-making, and mutual support fared the best in the aftermath of their baby's death.